Oxford handbook of reproductive medicine and family planning - McVeigh, Enda; Homburg, Roy; Guillebaud, John (Oxford handbooks., 2008)
This handbook provides practical, evidence-based guidance on the care of adolescents, reproductive age females, and males. Divided into three sections, it follows chronological age up to the menopause, covering areas such as the reproductive system puberty, the menstrual cycle, contraceptive methods, and infertility.